Measles virus and C3 binding sites are distinct on membrane cofactor protein (CD46). - Manchester, M (1995)
The human complement regulatory protein membrane cofactor protein (CD46) is the cellular receptor for measles virus (MV), whereas decay accelerating factor (DAF; CD55), a structurally similar complement regulatory protein, does not bind MV. To characterize the interaction between MV and CD46, mutants of the CD46 protein and hybrid molecules between CD46 and DAF were tested for their ability to act as MV receptors. The transmembrane domain and cytoplasmic tail of CD46 were not required for receptor function as cells expressing the CD46 extracellular domain linked to the glycosyl-phosphatidylinositol tail of DAF were rendered susceptible to MV infection. Chimeric proteins exchanging the four extracellular short consensus repeat (SCR) domains between CD46 and DAF indicated that only molecules with both SCR1 and SCR2 from CD46 allowed a productive MV infection. Further, monoclonal antibodies (mAbs) against SCR1 or SCR2 of CD46 blocked MV infection, whereas a mAb against SCR3 and SCR4 did not. The latter mAb blocks C3b/C4b binding (which maps to SCR3 and SCR4) whereas the former mAbs do not. Thus, our data indicate that both SCR1 and SCR2 make up the MV receptor determinant in CD46. These results also suggest avenues for development of therapeutic agents to inhibit MV binding and thus infection and disease.